2003
DOI: 10.1109/tkde.2003.1245290
|View full text |Cite
|
Sign up to set email alerts
|

Itemset trees for targeted association querying

Abstract: Association mining techniques search for groups of frequently co-occurring items in a market-basket type of data and turn these groups into business-oriented rules. Previous research has focused predominantly on how to obtain exhaustive lists of such associations. However, users often prefer a quick response to targeted queries. For instance, they may want to learn about the buying habits of customers that frequently purchase cereals and fruits. To expedite the processing of such queries, we propose an approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 25 publications
(33 reference statements)
0
63
0
Order By: Relevance
“…Aggarval et al . (2002) and Kubat et al . (2003) identified association rules from market basket analysis.…”
Section: Researches On Crm Using Data Mining Techniquesmentioning
confidence: 96%
“…Aggarval et al . (2002) and Kubat et al . (2003) identified association rules from market basket analysis.…”
Section: Researches On Crm Using Data Mining Techniquesmentioning
confidence: 96%
“…Raghavan, J.R. Lekkala, W.K. Chen introduce [2] concept of item-set Trees for Targeted Association Querying. In this paper we can have faster detection of item-sets and association rules.…”
Section: Related Workmentioning
confidence: 99%
“…There are several capable algorithms to insert transactions into the item-set tree and to count frequencies of item-sets for queries about power of association among items. [2] One of the efficient tree structures is memory efficient itemset tree. An efficient data structure for performing targeted queries for item-set mining and association rule mining is the MEIT.…”
Section: Introductionmentioning
confidence: 99%
“…Adomavicius and Tuzhilin (2001) examined association rules for one to one marketing. Aggarval and Yu (2002) and Kubat et al (2003) identified association rules from market basket analysis. Changchien et al (2004) …”
Section: Data Mining For Customer Relationship Managementmentioning
confidence: 99%